Ocular Trauma in Operation Iraqi Freedom and Operation Enduring Freedom from 2001 to 2011: A Bayesian Network Analysis. (4th July 2021) - Harvey, Morgan M.; Justin, Grant A.; Brooks, Daniel I.; Ryan, Denise S.; Weichel, Eric D.; Colyer, Marcus H.
ABSTRACT: Purpose: To update the epidemiology of ocular injuries in soldiers admitted to Walter Reed Army Medical Center (WRAMC) from 2001 to 2011 after sustaining combat injuries in Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF). Methods: Data were collected in the Walter Reed Ocular Trauma Database. A Bayesian Network Analysis was completed to better understand the relationships between different ocular demographic variables, injuries, surgeries, ocular trauma scores (OTS) and visual outcomes. Results: There were 890 consecutive globe or adnexal combat injuries, or both, sustained by 652 United States soldiers treated at WRAMC between 2001 and 2011.The primary mechanism of injury was improvised explosive device (62.47%). Many patients (62.0%) had final visual acuity (VA) grades of 1–2 (20/15 – 20/200), while 29.9% of patients had final VA grades of 3–5 (less than 20/200), and 8.1% had unknown final VA grades. Bayesian Network Analysis revealed that the injury variables of Retina (47.9%), Lens (44.6%), Posterior Segment (43.7%) and Anterior Segment (40.3%), and the surgical variables of Enucleation (97.6%) and cataract extraction and posterior capsule intraocular lens placement (CEPCIOL; 43.3%) all had probabilities greater than 40% for a poor final VA, while all other variables were less than 40%. Conclusion: Modern-day combat trauma results in complicated ocular injuries causing 30% of patients to be left legally blind in their injured eye. It is critical to maintain a wide variety of deployable, specialty trained ophthalmologists to ensure the best visual outcomes for wounded warriors and to maintain mission readiness.